Keterampilan Membaca Pemahaman Siswa Kelas IV Sekolah Dasar Dalam Mengikuti Program Literasi: Reading Comprehension Skills Of IV Grade Elementary School Students In Participating In The Literacy Program - Widyahningrum Febrianti; Lilik Binti Mirnawati; Meirza Nanda Faradita (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to analyze the reading comprehension skills of fourth grade students at SD Muhammadiyah 24 Surabaya while participating in the literacy program. This study also uses descriptive qualitative research with data collection techniques and triangulation techniques and sources. The data collection technique was triangulation technique, namely observation, interviews and documentation, while the source triangulation used was students and homeroom teachers for grade IV and school principals. The data analysis is a qualitative data analysis technique through the reduction stage, data presentation and the final stage is drawing conclusions or verification. The results of the study showed that there was an increase and change in students' reading comprehension skills after participating in the literacy program held by the school as seen from students being able to capture reading content, summarizing reading content, answering questions according to reading content and students being able to retell reading content. The supporting and supporting factors for the implementation of the literacy program are the human resources, namely students, teachers and schools.